2019
DOI: 10.1155/2019/8478750
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Citrate Influences Production of TNF-α in Healthy Men Lymphocytes

Abstract: The aim of our study was to determine whether sildenafil citrate influences the production of Th1- (TNF-α, INF-γ) or Th2-type (TGF-β, IL-10) cytokines by lymphocytes of healthy men. Sildenafil citrate (SC) is a selective blocker of phosphodiesterase 5, by competing for the binding site with cGMP. It was reported that a higher risk of sexually transmitted diseases (STD) could be correlated with a recreational use of sildenafil, especially when combined with another drug. While behavioral causes of these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…It was also reported that sildenafil reduced ionized calcium-binding adapter molecule 1 (Iba-1), IFN-γ, and IL-1β levels in an inflammatory demyelination model in INOS knockout mice [ 61 , 63 ]. We did not notice such a phenomenon concerning idNK cell cultures in the current research as well as in our previous research, SC did not influence the percentage of T lymphocytes producing IFN–γ in the PBMC cultures in healthy men [ 64 ].…”
Section: Discussionsupporting
confidence: 44%
“…It was also reported that sildenafil reduced ionized calcium-binding adapter molecule 1 (Iba-1), IFN-γ, and IL-1β levels in an inflammatory demyelination model in INOS knockout mice [ 61 , 63 ]. We did not notice such a phenomenon concerning idNK cell cultures in the current research as well as in our previous research, SC did not influence the percentage of T lymphocytes producing IFN–γ in the PBMC cultures in healthy men [ 64 ].…”
Section: Discussionsupporting
confidence: 44%
“…Isolated mouse splenocytes without red blood cells or tumor infiltrating lymphocytes (TILs) were stimulated in the presence of 50 ng/ml Phorbol 12-Myristate 13-acetate (PMA) (Sigma-Aldrich, St. Louis, MO) and 2 µM Ionomycin (Sigma-Aldrich), and treated with BD Golgi Stop (BD Biosciences, San Jose, CA) for 6 h at 37 °C in a humidified atmosphere of 5% CO 2 13 , 40 . After the culture, the cells were stained with fluorescent dye and monoclonal antibodies (mAbs): Zombie Aqua, CD3 (BV521), and CD8 (APC/Fire) mAbs (BioLegend, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…It binds to the cGMP site, reduces the content of TNF-α, and shows a tendency to decrease IFN-γ. 23 According to the research carried out by Elbardisy, 24 certain therapeutic effects can be achieved by intranasal application of tadalafil, such as significantly reducing the content of inflammatory factors in serum of subjects, reducing inflammation and oxidative stress, and alleviating various biochemical indicators of patients with metabolic diseases. 25 …”
Section: Discussionmentioning
confidence: 99%
“…It binds to the cGMP site, reduces the content of TNF-α, and shows a tendency to decrease IFN-γ. 23 According to the research carried out by Elbardisy, 24 certain therapeutic effects can be achieved by intranasal application of tadalafil, such as significantly reducing the content of inflammatory factors in serum of subjects, reducing inflammation and oxidative stress, and alleviating various biochemical indicators of patients with metabolic diseases. 25 It is shown in our study results that TNF-a, CRP and IL-6 in the experimental group are significantly lower than those in the control group after treatment, with statistically significant differences (TNF-a, p=0.01, CRP, p=0.00, IL-6, p=0.03).…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%